The Law Reports Kings Bench Division 1932 Vol 1 (London : Butterworths, 1974)
"An engraving showing a room of which the windows are strongly barred..." (Source: Stephens)
Related to event dated June, 1770 in Stephens.
This record contains unverified data from Stephens.
Catalogue of prints and drawings in the British Museum. Division I, political and personal satires / prepared by Frederic George Stephens
Forms part of: British Cartoon Prints Collection (Library of Congress).
Keywords: Cartoons (Commentary) -- British -- 1770.; Engravings -- 1770.